Optimal Placement and Sizing of Wind Turbines in Distribution Networks Using the GAO Algorithm for Power Loss Reduction - Phạm Minh Công; Nguyễn Công Minh; Phan Đình Chung (Journal of Technical Education Science, 2025)
This paper aims to determine the optimal placement and sizing of wind energy-based generators in a distribution network to reduce power/ electrical energy losses. To achieve the above-mentioned goal, in this research, historical wind data are utilized to identify the appropriate type of wind turbine that should be installed at each bus. Subsequently, the Green Anaconda Optimization (GAO) algorithm is developed to determine the optimal locations, number of turbines, and power factors at these sites. The proposed method is coded in MATLAB software, and then we use this code to test the standard IEEE 33-bus distribution system. The testing results indicated the location, number of turbines, rated capacities, power factors of the turbines that should be installed, and the resulting electrical energy loss in the network, which is lower than that without these wind turbines. The comparison result with other studies indicates that the energy loss in our research is lower.